PERHITUNGAN SUBSIDI PUPUK 2004 BERDASARKAN ALTERNATIF PERHITUNGAN SUBSIDI ATAS BIAYA DISTRIBUSI - MOHAMAD MAULANA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
Economic crisis was decreasing farmer income. At the end, its would be difficult for thefertilizer producers to stabilized production for domestic supply. For stabilizing fertilizerproduction and price, it is necessary to government to subsidized fertilizer. This objective of thisassessment was calculated the fertilizer subsidy through the distribution cost subsidy calculationmethod for 2004 compare to government fertilizer subsidy budget for 2004, Rap. 1.3 trillion. Theresult showed in 2004 the government had to budgeted about Rp. 1.64 trillion for fertilizersubsidy. In the other calculation using 2004 distribution cost and fee for distributor, the fertilizersubsidy increased to Rp. 1.875 trillion. This calculation bigger than the government fertilizersubsidy budget for 2004. It is necessary to reallocate the government budget for fertilizer subsidyand stabilized exchange rate for stabilizing fertilizer production and price at farmer level.